The Association of Stone Opacity in Plain Radiography with Percutaneous Nephrolithotomy Outcomes and Complications - Maghsoudi, Robab; Etemadian, Masoud; Kashi, Amir Hossein; Ranjbaran, Alireza (Urology Journal, 2016)
Purpose: To investigate the influence of stone opacity in plain radiography on stone free rate and complications ofpercutaneous nephrolithotomy (PCNL). Materials and Methods: A number of 101 patients who underwent PCNL between July-September 2015 wereprospectively included. Stone opacity was judged on preoperative plain Kidney-Ureter-Bladder X-ray. Stone freerate was evaluated two weeks after the operation by ultrasonography and KUB. Results: There were 61 patients with opaque stones and 40 patients with non-opaque stones. The age, body massindex, preoperative creatinine, history of stone surgery, and stone size was not statistically different betweenpatients with opaque and non-opaque stones. Neither operation duration nor access numbers were statisticallysignificant between opaque and non-opaque stones. The frequency of stone free patients in opaque stones and nonopaquestones were 55/61 (90%) and 30/40 (75%) respectively (P = .04) The magnitude of hemoglobin drop inopaque stones and non-opaque stones were 1.9 ± 1.2 mg/dL versus 2.9 ± 1.7 mg/dL (P = .005). Conclusion: The stone free rate is lower and the magnitude of bleeding is higher in PCNL of non-opaque stoneswhen compared to opaque stones if rigid instruments are used for nephroscopy.